Explaining Public Service Quality at the Village Level: Administrative Capacity, Transparency, Digitalization, and Citizen Participation - Zulfachry, Zulfachry; Rachmat, Zul (PUBLICUS: Jurnal Administrasi Publik, 2026)
Public service quality at the village level is a key indicator of governance effectiveness, citizen satisfaction, and institutional legitimacy, particularly in decentralized administrative systems. In Indonesia, village governments act as the frontline of public administration, delivering essential services such as population administration, civil registration, and community development facilitation. Despite decentralization reforms and increased fiscal authority, variations in service quality across rural villages remain a persistent challenge. This study investigates the determinants of public service quality in Goarie Village, Soppeng Regency, South Sulawesi. It examines the influence of human resource capacity, transparency and accountability of village fund management, digital administration implementation, and community participation. A quantitative explanatory approach was applied using a cross-sectional survey design. Data were collected from 120 residents who had accessed village administrative services within the previous twelve months. Structured questionnaires were used to capture citizens’ perceptions, and the data were analyzed through descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results suggest that governance and administrative factors play a significant role in shaping perceived public service quality. Human resource capacity and community participation emerged as the most influential determinants, emphasizing the importance of administrative competence and citizen engagement. Transparency and accountability also contributed positively, while digital administration showed a supportive but comparatively moderate effect. These findings highlight the multidimensional nature of village-level service quality and the need for integrated governance strategies.